EZH2 Protein Expression and Tumor Response to Neoadjuvant Chemotherapy in Locally Advanced Breast Cancer - Neusquen,Lucienne Pereira Del Grossi (2016)
Abstract Introduction Neoadjuvant chemotherapy (NAC) is the standard treatment for locally advanced breast cancer. However, some tumors will not respond to this treatment due to histological and molecular features. The protein EZH2 (enhancer of zest homolog 2) is a histone methyltransferase that is correlated with poorly differentiated breast carcinomas and aggressive tumor behavior. Purpose The present study evaluated the association between EZH2 expression and response to NAC, and its correlation with HER2 overexpression, estrogen and progesterone receptors (ER, PR) and Ki-67 proliferation index. Methods A total of 60 patients with locally advanced breast cancer treated with NAC were selected for this study. Twenty-three paraffin blocks had not enough material for tissue resection, and were not evaluated. A tissue microarray based in immunohistochemistry (IHC) analysis of EZH2 was performed for the remaining 37 specimens. Patients were divided into two groups based on response to NAC. Results EZH2 expression was significantly associated with markers of poor prognosis such as ER negativity (p = 0.001), PR negativity (p = 0.042) and high Ki-67 proliferation index (p = 0.002). High EZH2 expression was not correlated with the response to NAC. Conclusions Our data suggested that EZH2 protein expression may not correlate with the clinical response to NAC. Other studies with more patients are needed to confirm this observation.